AKIBAT HUKUM TERHADAP JAMINAN YANG DIBEBANI HAK TANGGUNGAN MELALUI AKTA SKMHT YANG DIPALSUKAN” (Studi Putusan Nomor : 395/PDT.G/2011/PN.JKT.SEL ) - RAFIKA DWI KURNIA TANJUNG (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budiman Ginting, SH, MHum'2.  Notaris Dr. Suprayitno, SH, MKn3.  Dr. T. Keizerina Devi A, SH, CN, MHum SKMHT (Hypothecation Imposition Letter) is used to make a hypothecation Certificate when its giver cannot be present. Guaranty imposition tends to reveal bad intention by falsifying SKMHT. The objective of the research is to analyze the forgery based on the problems of how about guaranty imposition can be done by using power of attorney of SKMHT, how about the legal consequence of the collateral which is imposed by Hypothecation through falsified SKMHT certificate, and about the judge’s legal consideration concerning the Verdict No. 395/Pdt.G/2011/PN.Jkt.Sel. The data were analyzed qualitatively by using figures, but is based on legal provisions and respondents’ answers in order to solve the problems in the research. The result of the research shows that SKMHT is a special power of attorney is used to make APHT (assignment of hypothecation certificate); principally, assignment of hypothecation has to be done by its giver and its receiver before a PPAT (official empowered to draw up land deeds) in making APHT, but when its giver cannot be present before PPAT, he is required to appoint another man on behalf of him in making SKMHT.Keywords: Deed, Power of Attorney for Hypothecation Imposition, Imposition